Multimodal Discourse Analysis on Black Panther: Wakanda Forever Movie Poster - Harjantoko, Lalu Angger; Djiwandono, Patrisius Istiarto; Ginting, Daniel (English Department of Faculty of Tarbiyah and Teacher Training, 2024)
Communication strategies in the modern period have become progressively multimodal with technological advancement. Multimodal communication involves forming a meaning through several modes than just language. This includes verbal and non-verbal communication, such as movie poster. Movie poster is one of the most effective promotional techniques to introduce the movie to potential audiences. Movie posters feature verbal and visual language as communication modes that can be interpreted to a certain meaning, including the movie’s theme, plot, and message. The visual grammar theory by Kress and van Leeuwen (2006) propose metafunctions to analyze image, including representational meaning. In representational meaning, communication modes must be able to represent elements and their relations in a world outside of their representational system as perceived by people. This paper demonstrates how various modes in “Black Panther: Wakanda Forever” movie poster are integrated to represent meaning and symbolism in the movie through representational meaning.